2010
DOI: 10.1002/gps.2411
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of depression and its correlates in early onset dementia patients

Abstract: We found a high occurrence of depressive symptoms in EOD patients; 65.7% of all our patients had some degree of depression. A history of depression was the most important correlate of depression in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
50
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 50 publications
8
50
2
3
Order By: Relevance
“…Depression is a common and disabling disorder in later life [13,27], and while subjects with depression have been reported to have significantly lower scores for activity of daily living (ADL) and quality of life (QOL) than those without depression [28], depression in the elderly has also been reported to be associated with poor cognitive function [29], dementia [30], developing AD [31], premotor symptoms in PD [32], and cerebrovascular disease [33]. Viewing these findings together with the organic pathological changes of the brain, leads us to believe that such brain changes may influence both the mood as well as motor function of the elderly who only have mild symptoms of neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is a common and disabling disorder in later life [13,27], and while subjects with depression have been reported to have significantly lower scores for activity of daily living (ADL) and quality of life (QOL) than those without depression [28], depression in the elderly has also been reported to be associated with poor cognitive function [29], dementia [30], developing AD [31], premotor symptoms in PD [32], and cerebrovascular disease [33]. Viewing these findings together with the organic pathological changes of the brain, leads us to believe that such brain changes may influence both the mood as well as motor function of the elderly who only have mild symptoms of neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is also within the range of 25-66% reported in four separate studies of community-based populations (vs. institutionalized or hospitalized) with diagnosed dementia that have employed different instruments to assess depressive symptomatology. Specifically, a 25% prevalence rate of depressive symptoms as assessed with the Cornell Scale for Depression in Dementia (CSDD) was reported in a study of memory clinic patients diagnosed with dementia due to AD [33]; among individuals diagnosed with probable AD dementia, a prevalence rate of 40% was reported as assessed with the Columbia University Scale for Psychopathology in Alzheimer's Disease (CUSPAD) [34]; a 49% prevalence rate of depressive symptoms was assessed with the Montgomery-Åsberg Depression Rating Scale (MADRS) among individuals referred to outpatient clinics specializing in geriatrics and older psychiatry diagnosed with a dementia type [35], and a prevalence rate of 66%, also assessed with the MADRS, was reported in a study of memory clinic patients diagnosed with early-onset dementia [36]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that younger dementia patients may display more neuropsychiatric problems, specifically affective symptoms, because a dementia diagnosis at a young age can result in more unexpected loss of independence and isolation [9,10]. However, the few studies comparing YO-AD with late-onset AD (LO-AD) have shown equivocal results.…”
mentioning
confidence: 91%